Factors Affecting Employee Performance at the Ministry of Health Republic of Indonesia - Ratih Ayu Sekarini; Agustin Widyaningsih; Lisa Putri Khairani; M Arya Dirgantara (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine how much influence job satisfaction, motivation, and leadership style have on employee performance at the Indonesian Ministry of Health. The research method used is a quantitative method with 51 respondents. The data collection techniques used are company observation, interviews with one of the company's employees, and distributing questionnaires using google form. in the calculation Data analysis is carried out using the Partial Least Square (PLS) method using Smart PLS version 4 software. The data analysis techniques used are validity test, reliability test, Structural Model Test test, and hypothesis. From the results of the study, it shows that job satisfaction, motivation, and leadership style have a significant effect on employee performance at the Indonesian Ministry of Health. from the tabulation data and diagrams of the final results of the questionnaire, the majority of respondents agreed with the statement that job satisfaction, motivation, and leadership style affect employee performance at the Indonesian Ministry of Health